Analysis of Sanitation Hygiene and Coliform Bacteria Content in Drinking Water Depots: A Cross-Sectional Study in Jember Regency - Erwan Widiyatmoko; Enny Suswati; Hadi Prayitno (Gema Lingkungan Kesehatan, 2025)
Effective Water, Sanitation, and Hygiene (WaSH) management is critical in emergency settings to prevent outbreaks of diarrheal diseases and reduce the total disease burden. Sanitary hygiene of drinking water depots is an effort to control risk factors for contamination from raw water, places, equipment and drinking water depot handlers so that drinking water depot products are safe for consumption. The study aimed to analyze the relationship between sanitary hygiene of drinking water depots to the content of coliform bacteria in drinking water depot products. Research used was the cross-sectional method is analytical descriptive. The sample calculation formula used was Lemeshow, obtaining 80 samples from a population of 432 drinking water depots. Sampling was done using proportional sampling techniques. The variables studied were raw water sanitation hygiene, place, equipment, drinking water depot handlers and total coliform bacteria. The statistical test uses the Rank Spearmen test to test whether there is a relationship between variables. The results showed that among the 80 drinking water depots, there were 67 (83.4%) drinking water depots that met the requirements for the total amount of coliform and 13 (16.6%) did not meet the requirements for the total amount of coliform. The results of the statistical test showed the significance value of raw water (p=0.000), equipment (p=0.000), handler (p=0.000) and place (p=0.885). The study showed that there was a significant relationship between raw water, equipment and handling of drinking water depots sanitation hygiene with the content of coliform bacteria in drinking water depot products, there was no significant relationship between drinking water depot places sanitation hygiene and coliform bacteria content in drinking water depot products. Further research can add other variables that affect the quality of drinking water depot products.